The questions on this page are similar to ones you will see on this lesson's quiz. Answer all of these questions, and read the feedback carefully. If you don't understand why one of your answers was incorrect, review that part of this lesson.
What is the measure of angle x? Decide which property or theorem applies, and create an equation to solve the problem.
- 99°
- 96°
- 53°
- 63°
Use the triangle sum theorem to solve the following equation:
x + 96 + 21 = 180
x + 117 = 180
x = 63°
Use the triangle sum theorem to solve the following equation:
x + 96 + 21 = 180
x + 117 = 180
x = 63°
Use the triangle sum theorem to solve the following equation:
x + 96 + 21 = 180
x + 117 = 180
x = 63°
Use the triangle sum theorem to solve the following equation:
x + 96 + 21 = 180
x + 117 = 180
x = 63°
What is the measure of angle x in this triangle? Decide which property or theorem applies, and create an equation to solve the problem.
- 85°
- 75°
- 70°
- 65°
Use the triangle sum theorem to solve the following equation:
x + 52 + 43 = 180
x + 95 = 180
x = 85°
Use the triangle sum theorem to solve the following equation:
x + 52 + 43 = 180
x + 95 = 180
x = 85°
Use the triangle sum theorem to solve the following equation:
x + 52 + 43 = 180
x + 95 = 180
x = 85°
Use the triangle sum theorem to solve the following equation:
x + 52 + 43 = 180
x + 95 = 180
x = 85°
What is the measure of angle x? Decide which property or theorem applies, and create an equation to solve the problem.
- 40°
- 45°
- 60°
- 90°
Use the triangle sum theorem to solve the following equation:
x + x + x = 180
3x = 180
x = 60°
Use the triangle sum theorem to solve the following equation:
x + x + x = 180
3x = 180
x = 60°
Use the triangle sum theorem to solve the following equation:
x + x + x = 180
3x = 180
x = 60°
Use the triangle sum theorem to solve the following equation:
x + x + x = 180
3x = 180
x = 60°
Find the value of x for this triangle.
- 20
- 27
- 32
- 40
Use the triangle sum theorem to solve the following equation:
(3x – 17) + (x + 40) + (2x – 5) = 180
6x + 18 = 180
6x = 162
x = 27
Use the triangle sum theorem to solve the following equation:
(3x – 17) + (x + 40) + (2x – 5) = 180
6x + 18 = 180
6x = 162
x = 27
Use the triangle sum theorem to solve the following equation:
(3x – 17) + (x + 40) + (2x – 5) = 180
6x + 18 = 180
6x = 162
x = 27
Use the triangle sum theorem to solve the following equation:
(3x – 17) + (x + 40) + (2x – 5) = 180
6x + 18 = 180
6x = 162
x = 27
Find the missing angle x. (For this problem, you'll need to apply what you've learned about exterior angles.)
- 25°
- 55°
- 105°
- 115°
Use the exterior angle theorem to solve for x.
x = 25 + 80
x = 105°
Use the exterior angle theorem to solve for x.
x = 25 + 80
x = 105°
Use the exterior angle theorem to solve for x.
x = 25 + 80
x = 105°
Use the exterior angle theorem to solve for x.
x = 25 + 80
x = 105°
Find the missing angle x. Apply what you've learned about exterior angles.
- 86°
- 58°
- 30°
- 28°
Use the exterior angle theorem to solve for x.
x = 28 + 58
x = 86°
Use the exterior angle theorem to solve for x.
x = 28 + 58
x = 86°
Use the exterior angle theorem to solve for x.
x = 28 + 58
x = 86°
Use the exterior angle theorem to solve for x.
x = 28 + 58
x = 86°
Summary
Questions answered correctly:
Questions answered incorrectly: